VARIASI PADAT PENEBARAN DAN PENGGUNAAN LARUTAN DAUN KETAPANG (Terminalia catappa L) TERHADAP PERTUMBUHAN BENIH IKAN NILA (Oreochromis niloticus) - Laini Anugraheni; Elrifadah Elrifadah; Yulius Kisworo (EnviroScienteae, 2022)
This study aimed to determine the effect of stocking density, the dose of ketapang leaf solution (Terminalia catappa L.) and the interaction between stocking density and dose of ketapang leaf solution (Terminalia catappa L.) on the growth of tilapia fish (Oreochromis niloticus). This research was conducted in July-August 2022 for 30 days, located on Jl RO Ulin Gang Sapta Warga Rt.07 Rw.02 Banjarbaru City. This study used a factorial completely randomized design method with 2 levels of Factor A (10 and 15 stocking densities) and 2 levels of Factor B (dose of ketapang leaf solution 2ml/l and 3 ml/l) with 3 repetitions (2x2x3). The treatments obtained were A1B1 (10 stocking density and 2ml/l ketapang leaf solution), A1B2 (10 stocking density and 3ml/l ketapang leaf solution), A2B1(15 stocking density and 2ml/l ketapang leaf solution dose). ) and A2B2 (stocking density of 15 individuals and the dose of ketapang leaf solution was 3ml/l). The fish used is tilapia seeds measuring 3-5 cm. In the results of the stocking density study, the dose of ketapang leaf solution had no significant effect on absolute growth and relative growth of tilapia fry. However, the interaction between stocking density and dose of ketapang leaf solution had a significant effect on the survival of tilapia.